International law, new diplomacy and counterterrorism : an interdisciplinary study of legitimacy - Barela, Steven J., 1971- (Abingdon, Oxon : Routledge, 2014)
'This interdisciplinary book explores how those who employ terrorist tactics across international borders intend to achieve their strategic goals by targeting a government's legitimacy. Because legitimacy must be bestowed through compliance from below, a shift away from the traditional top-down approach must be undertaken to account for the views of citizens. The spheres of legality, morality and efficacy serve to conceptualize legitimacy as this target of terrorism. To explore this hypothesis, the author uses the framework of international law to investigate the case study of the cross-border'war on terror' launched by the United States.Thus this work represents the conscious integration of two disciplines: international law and political philosophy. Through their integration, we see that civil societies have often turned to the standards of international law to understand and judge the legitimacy of their government's counterterrorism policies reaching across international borders. The end result is that counterterrorism's long-term effectiveness hinges on adopting policies which take into account international obligations based not only in codified legality, but in morality and efficacy as well. As the first element is the modern language of diplomacy and the other two have deep roots in diplomatic relations, this tripartite relationship has direct diplomatic implications. In essence, this is a book about'legitimate' counterterrorism policy. The author's concept of legitimacy as a target illuminates the need for placing legitimacy at the center of counterterrorism studies, and the book explores its shape and utility as an analytical tool through the application of three intersecting conceptual lenses.This book will be of much interest to students of international law, diplomacy, counter-terrorism, political philosophy, security studies and IR'--
Introduction: The Genii of the City -- Conceptualizing Legitimacy as a Target -- International Counterterrorism and a Legitimacy Deficit -- Through the Lens of Legality: Detention without Judicial Review -- Through the Lens of Morality: Just War and Public Diplomacy -- Through the Lens of Efficacy: Torture on Suspicion -- Conclusion: Jeopardizing Legitimacy and the Drones.
Includes bibliographical references and index.
Keywords: Terrorism (International law); Terrorism -- Prevention -- Law and legislation; War on Terrorism, 2001-2009.